Optical microangiography provides correlation between microstructure and microvasculature of optic nerve head in human subjects - An, Lin (Society of Photo-Optical Instrumentation Engineers, 2012)
It is demonstrated that optical microangiography (OMAG) is capable of imaging the detailed microstructure and microvasculature of the in vivo human optic nerve head (ONH), including the prelaminar tissue, the lamina cribrosa, the scleral rim and the vessels in the region of the circle of Zin-Haller. For demonstration, an ultrahigh sensitive OMAG system operating in the 850 nm wavelength region and a 500 kHz A-scan rate resulting in a spatial resolution of [Formula: see text] were used. It was shown that OMAG provides superior results for three-dimensional imaging of the ONH compared to conventional optical coherence tomography by simultaneously recording both the microstructure and the functional microcirculation. The blood supply to the tissues of the ONH is an essential physiologic parameter needed for clinical assessment of the health of the nerve.